Evolution of Block Level Sulphur Status and their Relationship with Some Physico-Chemical Properties of Soil of Raipur District, Chhattisgarh, India - Goswami, R.G.; Mishra, V.N.; Shrivastva, L.K.; Singh, A.K.; Kumar, Thaneshwar (Asian Journal of Chemistry, 2015)
A study on the evolution of block level sulphur status and their relationship with some physico-chemical properties of soil of Raipur district, Chhattisgarh, India was performed during 2014. Grid based soil samples from surface soils of Dharsiwa (54), Abhanpur (48), Tilda (54) and Arang (42) were collected using GPS and were analyzed to assess the status of available S and their relationship with some physico-chemical properties. The available sulphur (S) varied from 16.24 to 80.24 kg ha-1 with an average of 39.90 kg ha-1, found 7.40 % samples under low, 14.81 % in medium and 77.77 % in high status of sulphur and organic carbon level ranged from 0.24-0.96 (mean 0.60 %) at Dharsiwa block. Similarly, from Abhanpur block, available sulphur varied from 12.07 to 79.80 kg ha-1 with an average 43.94 kg ha-1 falls under low, medium and high categories as 8.33, 12.5 and 79.16 %, respectively and organic carbon varied from 0.23-0.96 (mean 0.60 %). In Tilda block, available sulphur varied from 8.68 to 97.72 kg ha-1 with an average 41.59 kg ha-1 and the per cent samples tested under low, medium and high status sulphur were found as 14.81, 11.11 and 74.07 %, respectively and organic carbon ranged from 0.23-0.96 (mean 0.75 %). In Arang block, available sulphur varied from 8.96 to 98.84 kg ha-1 with an average 38.83 kg ha-1 and the per cent samples tested under low, medium and high status sulphur were found as 14.28, 9.52 and 76.19 %, respectively and Arang organic carbon varied from 0.23-0.96 (mean 0.59 %). The analyzed data on sulphur level from Dharsiwa and Abhanpur block was correlated with soil pH and organic carbon levels indicated positive correlation with soil pH and positive with organic carbon status. Similarly Arang and Tilda block was recorded negative correlation with soil pH and positive correlation with organic carbon except Arang block. Soil nutrient index of all four selected blocks were found in high fertility classes for available sulphur, respectively.